Perylene π-bridges equally delocalize anions and cations: proportioned quinoidal and aromatic content - Mayorga Burrezo, Paula; Paula Mayorga Burrezo; Zeng, Wangdong; Moos, Michael; Holzapfel, Marco; Canola, Sofia; Negri, Fabrizia; Rovira, Concepciò; Veciana, Jaume; Phan, Hoa; Wu, Jishan; Lambert, Christoph; et al. (Wiley ; Gesellschaft Deutscher Chemiker, 2019)
A complete experimental and theoretical study has been carried out for aromatic and quinoidal perylene-based bridges, either substituted with bis(diarylamine) or bis(arylimine) groups. The through-bridge inter-redox site electronic couplings (VAB) have been calculated, for their respective mixed-valence radical cation and radical anion species. The unusual similitudes of the resulting VAB values for the given structures reveal the intervention of molecular shapes with balanced semi-quinoidal/semi-aromatic structures in the charge delocalization. An identical molecular object equally responding to the injection of positive or negative charges is rare in the field of organic πconjugated molecules. However, once probed herein for perylene-based systems, it can be extrapolated to others πconjugated bridges. As a result, this work opens the door to the rational design of true ambipolar bulk and molecular conductors.
Keywords: Radicales (Química); Reactividad (Química); Radicales; Reactividad química